Limb-Specific Features and Asymmetry of Nerve Conduction Velocity and Nerve Trunk Size in Human - Nobue, Ayaka; Kunimasa, Yoko; Tsuneishi, Hiromu; Sano, Kanae; Oda, Hiroyuki; Ishikawa, Masaki (Frontiers in Physiology, 2020)
This study aimed to simultaneously examine the differences of human nerve conduction velocity (NCV) and nerve cross-sectional area (nCSA) between the upper and lower limbs and between different regions of the upper and lower limbs. Thirty healthy subjects volunteered for the study. NCV and nCSA of the ulnar and tibial nerves were measured with the dominant and non-dominant arms and the supporting and reacting legs using supramaximal electric stimulation and peripheral nerve ultrasonography at three regions for ulnar and tibial nerves, respectively. Supramaximal electric stimulation was superficially applied to the ulnar and tibial nerves at each point. These action potentials were recorded from the digiti minimi and soleus muscles for the ulnar and tibial nerves, respectively. Our results clearly showed that the NCV, nCSA, and circumference of the ulnar and tibial nerves were higher and greater in the lower limbs than in the upper limbs. The greater the circumference, the greater the nCSA for both the upper and lower limbs. However, unlike the upper limbs, the supporting leg did not have higher NCV than the reacting leg despite its greater circumference. Therefore, nCSA can be related to the circumference, but not necessarily function for NCV developments of the lower limbs. These various aspects between the upper and lower limbs suggest that NCV does not depend on the nCSA sizes or upper and lower limb circumference; the results indicate the existence of limb-specific NCV, but not nCSA developments.